2021
DOI: 10.1097/wno.0000000000001473
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Abducens Nerve Palsy in Patients Undergoing Surgery for Petroclival Meningiomas

Abstract: Background:During the surgical resection of petroclival meningiomas, preserving the cranial nerves is crucial. The abducens nerve is particularly vulnerable during surgery. However, the preoperative risk factors and postoperative prognosis of abducens nerve palsy (ANP) are poorly understood.Methods:We retrospectively analyzed 70 patients who underwent surgery for petroclival meningiomas between May 2010 and December 2019, divided into gross-total resection (GTR) and subtotal resection (STR) groups. The relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Furthermore, an encasement of the abducens nerve at the dural entrance as well as close adhesions between arachnoid membranes of the nerve’s cisternal portion and the meningioma are also discussed [ 35 , 36 ]. A recent retrospective study of 70 patients who underwent PC MNG surgery found that the invasion of the internal auditory canal is a risk factor for postoperative abducens nerve palsy [ 37 ]. Auditory canal invasion was present in 21.9% of all patients in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an encasement of the abducens nerve at the dural entrance as well as close adhesions between arachnoid membranes of the nerve’s cisternal portion and the meningioma are also discussed [ 35 , 36 ]. A recent retrospective study of 70 patients who underwent PC MNG surgery found that the invasion of the internal auditory canal is a risk factor for postoperative abducens nerve palsy [ 37 ]. Auditory canal invasion was present in 21.9% of all patients in our study cohort.…”
Section: Discussionmentioning
confidence: 99%